A ligand-controlled switch of regioselectivity in ring-opening coupling of diarylmethylenecyclopropa[b]naphthalenes with Grignard reagents. Issue 2 (18th November 2015) - Cao, Jian; Huang, Xian; Wu, Luling
Abstract : A ligand-controlled regioselectivity switch of ring-opening coupling reaction of diarylmethylenecyclopropa[ b ]naphthalenes with Grignard reagents providing differently substituted β-vinylic naphthalenes in moderate to excellent yields was reported. Based on careful NMR study, we concluded that it may be explained by the ligand effect. Abstract : A ligand-controlled regioselectivity switch of ring-opening coupling reaction of diarylmethylenecyclopropa[ b ]naphthalenes with Grignard reagents providing differently substituted β-vinylic naphthalenes in moderate to excellent yields was reported: when Pd(OAc)2 was used, the aromatic group from the Grignard reagent regioselectively coupled to the naphthyl ring after the ring-opening of three-membered cycle, which is different from the Pd(PPh3 )2 Cl2 -catalyzed reaction. Based on a careful NMR study, we concluded that it may be explained by the ligand effect.